Numerical characterization of the performance of counter-flow double-pipe heat exchanger using nanofluids for laminar flow regime - Abdulaziz S. Alhulaifi (Results in Engineering)
Despite the discovery of the concentric double pipe heat exchanger almost a century ago, its applications for nanofluids is not properly understood. It enables the transfer of thermal energy between different fluids in a variety of practical applications. This study presents a numerical model of counterflow configurations of a concentric double-pipe heat exchanger operating in a laminar flow regime. A numerical model was created using the governing equations of conservation of continuity, momentum and energy under plausible assumptions. The numerical model was solved using the ANSYS Fluent® computational fluid dynamics (CFD) code, and the results were confirmed against available published numerical and experimental data. The findings revealed that increasing the internal Reynolds number had a direct impact on gaining a higher nanofluid Nusselt number. However, increasing the annular hot water Reynolds number had no significant impact on the nanofluid Nusselt number. Not only may increasing the internal Reynolds number enhance the nanofluid's Nusselt number, but also can lower nanoparticle thermal conductivity. In comparison to other nanofluids, lower density nanofluids, such Ash/H2O, had larger pressure drop and pumping power. The Buckingham Pi theorem was used to perform nondimensionalization analysis. A generalized solution for estimating the Nusselt number under a laminar flow regime for a wide nanofluid applications is proposed. Conclusions of the empirical equation were checked against available data, and the findings are extremely consistent, verifying the validity of Lambda function.